Identification Of Medicinal Products Made From Macro And Micro Algae In Traditional And Modern Markets In Medan City - Jihan Luthfi Nabilah; Moza Hanu Sabila; Rizki Bob Anggara; Susi Andani; Syarifah Widya Ulfa (Jurnal Multidisiplin Sahombu, 2024)
This study aims to identify and analyze medicinal products containing macro and micro algae as basic ingredients that are available in traditional and modern markets in the city of Medan. The descriptive survey method was used in this research, with data collection through direct observation, interviews with sellers and buyers, and product documentation. The markets surveyed included several representative traditional and modern markets in Medan City. The research results show that modern markets offer a wide range of algae-based products, whereas in traditional markets, these products may be more limited. Consumers in the modern market tend to be more aware of the health benefits of algae and prefer products that have clear certification and quality standards. However, consumer awareness in traditional markets still needs to be increased. Obstacles such as lack of consumer education and limited product distribution are still challenges that need to be overcome. Thus, an effective strategy in developing the market for algae-based medicinal products in Medan City is to increase consumer education, improve regulatory standards and product quality, and expand product distribution more evenly between traditional and modern markets.